1989
DOI: 10.1001/archderm.1989.01670140079014
|View full text |Cite
|
Sign up to set email alerts
|

Topical Methotrexate Therapy for Psoriasis

Abstract: In vitro percutaneous penetration of methotrexate is enhanced with 1-dodecylazacycloheptan-2-one (laurocapram [Azone]). Laurocapram-containing methotrexate formulations provide effective local inhibition of epidermal DNA synthesis in the in vivo hairless mouse and minipig models, providing the biochemical rationale for topical use in the treatment of psoriasis. Topical methotrexate (0.1%, 0.5%, and 1%) in a laurocapram-containing formulation was tested in a two-center double-blind pilot clinical study of 42 pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
29
0
2

Year Published

2001
2001
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 55 publications
(31 citation statements)
references
References 14 publications
0
29
0
2
Order By: Relevance
“…The magnitude of the overall response was limited, however, possibly due to the severity of disease in the study patients. Also, an earlier study by Weinstein et al 4 . indicated that there may be a greater difference between the active and placebo treatments when MAZ topical gel is applied twice daily rather than once daily, as was the case in this study.…”
Section: Discussionmentioning
confidence: 50%
See 2 more Smart Citations
“…The magnitude of the overall response was limited, however, possibly due to the severity of disease in the study patients. Also, an earlier study by Weinstein et al 4 . indicated that there may be a greater difference between the active and placebo treatments when MAZ topical gel is applied twice daily rather than once daily, as was the case in this study.…”
Section: Discussionmentioning
confidence: 50%
“…A previous double‐blind, vehicle‐controlled pilot study has demonstrated that topically applied MTX (0.1, 0.5, and 1.0%), in an Azone formulation, produces a 50% or greater improvement in psoriatic patients following 6 weeks of twice‐daily application 4 . Plasma concentrations of MTX were below the limits of detection throughout the course of the study.…”
Section: Introductionmentioning
confidence: 91%
See 1 more Smart Citation
“…The difference in the results is possibly due to the use of ethyl acetate along with ethanolic solution of menthol, which causes higher lipid extraction. Moreover, the flux in this study is much higher as compared to the other research groups [22][23][24][25][26][27][28][29] . However, direct comparison between the fluxes obtained with different research groups cannot be compared due to the different animal species and membrane employed for the study.…”
Section: Effect Of Chemical Enhancer and Square Wavementioning
confidence: 57%
“…MTX formulation as a hydrogel patch facilitates sustained drug release 22 in contrast to solution or gel 23 . Various researchers have reported the delivery of MTX by ointments, creams, gels, microemulsions, hydrogels, chemical enhancers, and DC iontophoresis 18,[22][23][24][25][26][27][28][29][30] . Our earlier publication 31 demonstrated the advantages of mDC iontophoresis on transdermal delivery.…”
Section: Introductionmentioning
confidence: 99%